2011
DOI: 10.1371/journal.pgen.1001365
|View full text |Cite
|
Sign up to set email alerts
|

An Evolutionary Genomic Approach to Identify Genes Involved in Human Birth Timing

Abstract: Coordination of fetal maturation with birth timing is essential for mammalian reproduction. In humans, preterm birth is a disorder of profound global health significance. The signals initiating parturition in humans have remained elusive, due to divergence in physiological mechanisms between humans and model organisms typically studied. Because of relatively large human head size and narrow birth canal cross-sectional area compared to other primates, we hypothesized that genes involved in parturition would dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
89
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 101 publications
(97 citation statements)
references
References 52 publications
2
89
1
5
Order By: Relevance
“…One SNP in FSHR gene (rs6165) showed a P value <0.05 in the gestation age <32-wk group and PPROM group, but did not reach formal levels of significance once corrected for multiple comparisons. Notably our results did not replicate the previously described associations of FSHR polymorphisms and PTB (19,20). In addition, SNPs in SERPINH1 did not show an association with PPROM cases as shown previously (21).…”
Section: Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…One SNP in FSHR gene (rs6165) showed a P value <0.05 in the gestation age <32-wk group and PPROM group, but did not reach formal levels of significance once corrected for multiple comparisons. Notably our results did not replicate the previously described associations of FSHR polymorphisms and PTB (19,20). In addition, SNPs in SERPINH1 did not show an association with PPROM cases as shown previously (21).…”
Section: Resultscontrasting
confidence: 99%
“…Familial trends and racial disparities of prematurity also suggest that genetics influence this trait (9)(10)(11). A number of case-control and family-based studies have evaluated candidate genes chosen from some of the pathways associated with PTB (12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is more commonly proposed that human gestation length and altriciality are a solution to the uniquely human "obstetrical dilemma" (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), also called the "obstetric dilemma" and, henceforth, referred to as OD. The OD hypothesis proposes that Pleistocene hominins faced antagonistic selection pressures on locomotor requirements and encephalization.…”
mentioning
confidence: 99%
“…These studies have traditionally focused on one or a few candidate genes, chosen based on our current understanding of physiology. More recently, genome-wide linkage analyses in families with recurrent PTB and large-scale association studies have revealed further susceptibility genes for PTB [9,21,24].…”
Section: Introductionmentioning
confidence: 99%